The effects of bottom ash in coastal sand - Youventharan, Duraisamy; Rokiah, Othman; S. M., Arif (2019)
In the construction industry, breakage of sand particles is very common especially at the very early stage of the pile driving work. The breakage of sand particles will result in change of size spectrum and alter its engineering properties. In this research, the effectiveness of bottom ash in improving the engineering properties of crushed sandy soil was studied. The bottom ash of 5%, 10%, 15% and 20% was added into the sand and crushed with 500 and 1000 blows under the Automatic Compactor machine. The engineering properties of different proportion of bottom ash mixture before crushing and after crushing with 500 and 1000 blows were tested. The engineering properties which were measured include the coefficient of uniformity, breakage index, fouling index, permeability and bearing capacity. Results show that adding of bottom ash into the crushable sand improved the load bearing capacity. By adding 20% of bottom ash, the bearing capacity of the crushed sandy soil can be improved by 55% meanwhile the permeability of the sandy soil can be improved by 200%.